Pastorałka dramatyczna Juliusza Słowackiego i jej muzyczna interpretacja we "Fragmentach" Zygmunta Mycielskiego - Mielcarek-Krzyżanowska, Barbara (Res Facta Nova, 2020)
Zygmunt Mycielski’s final work, Fragmenty to words by Juliusz Słowacki (1987) belongs to the collection of religious works which crown the creative path of the author of Postludia. Fragmenty were written on the basis of a rigorous, individual method of composing using twelve notes – an array system devised by him towards the end of the 1950s which from that time consistently accompanied his creative undertakings. The austerity of technique achieved by limiting external effects, particularly apparent in Mycielski’s religious compositions (alongside Fragmenty one should mention here above all Trzy psalmy and the mass Liturgia sacra), results from the desire to reject pathos in favour of gravity and simplicity. This conscious creative decision means that the devices used serve to bring out the meaning and the emotion in Słowacki’s text, and in the created narration one perceives authenticity, truth and modesty. Fragmenty may be interpreted as a special kind of testament, Mycielski’s confession of faith, and the shades of sacrality discovered in it – the stages of musical spirituality according to Bohdan Pociej’s conception, support this supposition.